First-principles investigation on the impact of copper concentration on zinc telluride as the back contact for cadmium telluride solar cells - Afiq Radzwan (Tanjung Malim, 2024)
First-principles investigation on the impact of copper concentration on zinc telluride as the back contact for cadmium telluride solar cells by Afiq Radzwan